A case of diffuse neonatal haemangiomatosis - Wickramasinghe, V. P.; Lamabadusuriya, S. P.; P A S S Dayawansa, P. A. S. S. (Sri Lanka college of pediatricians, 2004)
Haemangiomata are benign vascular tumours occurring during neonatal period. Multiple haemangiomata occur in about 25% of patients with haeman-gioma1. If they occur only in the skin, the entity is termed benign neonatal haemangiomatosis2. If the haemangiomata show systemic involvement, including visceral heaemangiomata, the term diffuse neonatal haemangiomatosis is used3.

Haemangiomata are benign vascular tumours occurring during neonatal period. Multiple haemangiomata occur in about 25% of patients with haeman-gioma1 . If they occur only in the skin, the entity is termed benign neonatal haemangiomatosis2 . If the haemangiomata show systemic involvement, including visceral heaemangiomata, the term diffuse neonatal haemangiomatosis is used3 .
Keywords: diffuse neonatal haemangiomatosis